Carotid arterial blowout after organ preserving chemoradiation therapy in hypopharyngeal cancer. Issue 45 (11th November 2022) - Padua, Paula Francezca; Fang, Hsuan-Yeh; Young, Chi-Kuan; Yeh, Chih-Hua; Lin, Chia-Chen; Liao, Chun-Ta; Chang, Tung-Chieh Joseph; Tsao, Chung-Kan; Huang, Shiang-Fu
Abstract : Laryngeal preserving concurrent chemoradiation has been advocated for hypopharyngeal cancers. The use of radiotherapy (RT) in the larynx could lead to increased rates of radionecrosis. In this study, we investigated a rare but disastrous complication, carotid blow-out syndrome (CBS), related with the persistent radionecrosis. Retrospective cohort study. This retrospective study enrolled hypopharyngeal cancer patients with biopsy-proven pharyngeal and laryngeal chondronecrosis (PLCRN), which was rated by the Chandler Grading System. From 2002 to 2018, a total of 346 hypopharygeal cancer patients received upfront radiation therapy, 13 PLCRN patients were identified in a rate of 3.8%. All PLRN patients received RT with a mean radiation dose of 70.81 ± 0.85 Gy. All patients had Chandler Grade IV at the time of presentation, which was a mean of 15.08 months (range: 5‐109 months) from the time of cancer diagnosis to PLCRN diagnosis. In 5 of the 13 PLCRN patients developed CBS. Three of the CBS originated from superior thyroid artery, one from lingual artery and one from the carotid artery. Three (60%) of the 5 CBS patients expired due to loss of airway and hemodynamic instability. Two (40%) were rescued by emergent airway secure and emergent angiographic embolization. Persistent PLCRN could lead to disastrous vascular complications. CBSs were demonstrated to be more frequently originated from the branches of carotid artery rather than carotid artery per se. Clinical alert with early airway protection could strive for time to do interventions and prevent mortalities.